P??ssaros sem asas: uma compreens??o sobre a educa????o em pris??es - Oliveira, Andr??a dos Santos (2019)
The present work discusses the education in the prisons and has as object of study the comprehension about the limits and possibilities of human development of the student in the context of deprivation of liberty. For this purpose, it has two objectives: to analyse the limits and possibilities of the human development in inmate-students, by means of the understanding of the structure, functioning, norms, rules, scenario and relations of the prison and the school, as well as to verify how the pedagogical work takes place and to comprehend how the process of education occurs through the vision of its participants. In this way, the formulated hypothesis is that the environment of rules and strict disciplines stands out in the school in prison, which restricts the aims of education and, as a result, the possibilities of human development. The theoretical framework is based on the complex thinking of Edgar Morin, demonstrating the categories of comprehension and incomprehension and dialogued with the Personalism of Emmanuel Mounier. The methodology refers to sources of documental and bibliographic nature and has, as developed procedure, the holding of semi-structured interviews with students and teachers of the prison unit Provisional Detention Center II ??? ASP Paulo Gilberto de Ara??jo de Ch??cara Bel??m II, in the city of S??o Paulo. It was also possible to observe the context of the facility that interacts with the school and its dynamics, which is the case of the relation between professionals, prison milieu and surroundings. The final outcome showed that incomprehension holds sway over the ambiance and prison education and, despite the perception of the inmates-students about the importance of building a life project and self-development, the political tools are not properly offered and discrimination, structure of power and physical and moral violence render their ability to grow impossible; and the teachers, even in the middle of adversity, are the only ones who support their progress, by offering them sympathy and understanding.